Relationship Between Nurses and Social Workers Perceptions of Medical Secretary Roles and Information-Sharing Behaviors: A Cross-Sectional Study - Saleh Enad Jalwe Alshmmri, Amina Makimi Mays Al-Dhafiri, Amani Makimi Miss Aldfiri, Intisar Nayef Kreidi Al-Dhafiri, Abdulaziz Thani Adeed Alshammri, Arif Raja Aldhafeeri (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Information-sharing plays a crucial role in providing effective inpatient care, especially between nurses and nursing assistants. Nurses who have a positive perception of the roles of nursing assistants are more likely to engage in productive information-sharing behaviors with them. This study investigates the correlation between nurses’ perceptions of nursing assistant roles and the frequency of information-sharing with nursing assistants. Data were gathered from 2,642 nurses across 182 hospitals using a self-administered cross-sectional survey questionnaire. The questionnaire included measures of nurses’ perceptions of nursing assistant roles across four factors: (i) enhancing patients’ abilities through daily care, (ii) caring for diverse patients with broad perspectives, (iii) facilitating coordination and cooperation within the team, and (iv) increasing information sharing among team members regarding patients. Information-sharing behaviors assessed included expressions, inquiries, linguistic responses, and feedback. Multiple regression analyses were performed to analyze each nurse’s information-sharing behaviors. The results indicated a positive correlation between nurses’ perceptions of nursing assistant roles and their frequency of information-sharing with nursing assistants. The strength of these correlations varied depending on the specific type of information-sharing behavior. Therefore, enhancing nurses’ understanding of nursing assistant roles could potentially enhance their information-sharing behaviors, contributing to more effective collaborative practices in healthcare settings.